(untitled) (Revista de Ciências Agroveterinárias, 2025)
Durum wheat (Triticum durum Desf.) plays a crucial role in Algeria’s agronomic sector, contributing significantly to the economy and food security. This study assesses the genetic effects and combining abilities of key agronomic traits using a 4 × 4 half-diallel mating design. The parents and their six F1 hybrids were evaluated during the 2021–2022 growing season in a randomized complete block design with three replications at INRAA Institute (Setif, Algeria). Eight morpho-agronomic traits —plant height (PH), spike length (SL), spikes weight (SW), number of spike plant−1 (NS), number of grains spike−1 (NGS), thousand kernel weight (TKW), grain yield (GY) and above-ground biomass (BIO)—were analyzed. Combining ability was assessed using GRIFFING’s Method 2, Model 1 to estimate the general combining ability (gca) and specific combining ability (sca) effects. Significant gca and sca effects were observed across all traits, confirming both additive and non-additive genetic influences. Additive gene effects predominated for PH, SL, and GY, while non-additive effects were more relevant for SW, NS, NGS, TKW, and BIO. Waha (P2) and Beni Mestina (P3) showed significant gca effects for PH, Achouri (P1) for SL and BIO, Beni Mestina (P3) for SW, NS, GY, and MBB (P4) for TKW, indicating their potential as good general combiners. Hybrids Achouri × Waha (H1) and Beni Mestina × MBB (H6) exhibited significant sca effects for PH, while Achouri × Waha (H1) also influenced SL and BIO. Additionally, Beni Mestina × MBB (H6), Achouri × MBB (H3), and Achouri × Waha (H1) exhibited notable sca effects for TKW, indicating complementary gene interactions. These findings provide insights into durum wheat’s genetic architecture, aiding in the selection of promising parents and hybrids for breeding programs. The results emphasize the complexity of hybrid performance prediction and highlight the importance of careful parental selection to enhance yield and related traits.